DEMOGRAPHIC PROCESSES AND THE LABOR MARKET IMPROVING INTERCONNECTION (Multidisciplinary Journal of Science and Technology, 2024)
Comprehensive scientific research aimed at developing the impact of demographic processes on the labor market in the world based on statistical analysis, including the impact of the demographic situation on the labor market, the impact of demographic processes on the regional economy, demographic changes on labor supply and economic growth Scientific research is being conducted in areas such as the effect on swelling. Based on these aspects, conducting scientific research on the statistical study of demographic processes and the interaction of the labor market is one of the urgent issues. This article addresses this and can be used by undergraduates, graduate students, independent researchers, and a wide audience.